Energy and performance costs evaluation for BLE mesh links - Silva, Henrique Carvalho; Margi, Cíntia Borges (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2018)
Bluetooth Low Energy (BLE for short) is among the favorites to become a de facto standard in the context of the Internet of Things (IoT). However, its main challenge is the lack of standards for efficient mesh networking. Furthermore, the literature lacks works analyzing energy consumption trade-offs for BLE mesh networks. We address this issue by experimentally evaluating three minimal topologies for linking separate BLE star networks. We aim to determine a lower boundary in terms of energy and performance costs using the metrics of energy consumption, delivery rate, and goodput. We perform our experiments using a testbed comprised of TI CC1350 nodes running Contiki OS. Our results enable us to estimate similar costs for large scale networks.